(untitled) (Al-Aasar, 2025)
Consumerism refers to a mindset that emphasizes the acquisition of non-essential goods rather than focusing on basic human needs. In Arabic, it is known as "Istihlak," while in Urdu, it is referred to as "Saarfiyat." The phenomenon of consumerism encompasses both positive and negative trends. On the positive side, it drives economic growth by increasing demand for goods and services, creates employment opportunities, promotes industrial development, and raises living standards. However, the negative aspects of consumerism include environmental issues caused by excessive production, health problems, mental stress, rising debts due to the desire for more spending, and the production of substandard goods by companies. In the present day, the pressure of consumerism has led to a host of societal problems, making it a global concern. Therefore, understanding the negative trends of consumerism and finding solutions to mitigate its effects has become essential. This paper will explore these issues and propose solutions based on Islamic economic principles to address them, offering a holistic approach to mitigating the adverse impacts of consumerism.